IDENTIFICATION AND RISK CONTROL OF THE HACCP SYSTEM IMPLEMENTATION IN THE PASTEURIZED CRAB PRODUCTION PROCESS - A. P. , Rezki Amelia Aminuddin; Hari Purnomo (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: In the production process, small accidents often occur between fellow workers in the production area, such as workers colliding with each other during the transfer process from one process to the next which causes the product to spill and workers fall, causing injury. PT. XYZ is a company engaged in the seafood industry, especially canning crabs. The company's production process applies a Good Manufacturing Practice (GMP) system with 12 work areas and 80% of the process is still done manually. Purpose: The purpose of this study is to identify risks and control the implementation of the HACCP system in the crab canning industry using the HAZOP method. Method: This type of research is a descriptive study, using the HAZOP (Hazard and Operability) method. The research was carried out at 12 nodes, namely receiving, checking aroma, sorting, mixing and filling, metal detecting, weighing, seaming, pasteurization, chilling, packing, and sanitation. Result: The results showed 4 risk ratings, namely low, medium, high, and extreme risk based on 8 sources of potential hazards. The biggest risk that is extreme is in node seaming. Conclusion: Based on processing data, 8 sources of potential hazards that can occur in the pasteurized crab meat production room. The recommendations given are to implement elimination, reduction, engineering control, administrative control, Personal Protective Equipment, work attitude improvement, and OHS training.